POLA MAKAN DAN GEJALA ANEMIA PADA MAHASISWA PERANTAUAN DI UNIVERSITAS SAMUDRA - Mufa, Nurul Aulia (Department of Biology Education, Faculty of Teacher Training and Education, Samudra University, 2020)
ABSTRACT Diet is a behavior that affects nutrition. The quality and quantity of food and beverages consumed will affect health. This causes nutritional deficiencies, a healthy and balanced diet is needed to support the smooth running of busy daily activities, such as overseas students. The purpose of this study was to examine the effect of diet with symptoms of anemia in overseas students. The method used is descriptive, namely by filling out a questionnaire on google form which contains 70 respondents. The results of this study 50 people 74.3% felt the symptoms of anemia 20 or 25.7% did not feel the symptoms of anemia. The thing that must be done so that anemia does not occur must be a change in diet. Keywords : Dietary habit, student of overseas and Anemi symtoms.